Academic integrity in a digital era: Should the use of ChatGPT be banned in schools? - Divine Ogugua; Seong No Yoon; Donhee Lee (Global Business & Finance Review (GBFR), 2023)
Purpose: This paper is to examine the ethical implications of the use of ChatGPT in academia. Design/methodology/approach: This study reviews the previous research and cases associated with using a generative AI, such as ChatGPT, to effectively use ChatGPT in education for teachers and students by examining the negative (especially ethical issues) and positive aspects of ChatGPT. Findings: The findings of this research are that the usage of ChatGPT in schools has both negative and positive aspects. The results of this study indicated that effectively incorporating ChatGPT into educational settings: 1) identify opportunities to integrate ChatGPT into the curriculum; 2) define the specific goals and objectives to be achieved using ChatGPT in classes; 3) establish clear guidelines and boundaries for using ChatGPT; and 4) emphasize the importance of critical thinking and independent problem-solving skills with ChatGPT. Research limitations/implications: Considering the lack of previous research on ChatGPT, the limitations of this study lie in the fact that it is not based on empirical research with actual data. Originality/value: This study suggests potential opportunities and challenges for educational institutions, students, policymakers, and users regarding the using ChatGPT.
Keywords: 650; ChatGPT; ChatGPT Ban; ChatGPT in Education; Academic Integrity